Acehnese People’s Information Seeking Behavior about COVID-19 - Rizanna Rosemary; Hamdani M Syam; Nur Anisah; Deni Yanuar; Heru Syah Putra (Ikatan Sarjana Komunikasi Indonesia, 2021)
This research aims to identify types of media used by the Acehnese people in seeking information about COVID-19, and people’s perceptions and responses to the information that increases their likelihood of the risk of the pandemic. This study employs a quantitative approach, in which an online survey distributed through social media. All 324 respondents gave their consent to participate in filling out the research questionnaire. The study found that Acehnese people prefer online media and television (TV) to receive information about COVID-19, especially when people can access the information online (streaming). The finding indicates that people tend to trust information obtained through the media more than direct information (face to face) conveyed by the government. Regarding the public responses, this study found that most respondents argue the lack of government action in disseminating information about COVID-19. It is believed that this condition is likely to bring up false information (hoax) from untrustworthy information sources. This response has an impact on the level of public trust towards the government as the main source of information in handling the pandemic. Respondents claim that the local government has a slow response in providing information about people who are infected by the virus, including insufficient information on the intervention of prevention and treatment carried out to stop the spread of the virus.